PC Tools Deluxe™ : the complete reference. - Bender, Hy (Berkeley, USA : Osborne McGraw-Hill, 1990)
"Hy Bender's new complete reference guide gives you a fast start with PC tools Deluxe versión 6 and a thorough. Wll organized and clearly written to help you get the most from our hardware. Through step-by-step instructions. PC Tools Deluxe™: the complete reference helps you quickly learn the fundamentals of this outstanding DOS-based program, including how to • Back up and restore your hard disk. • Recover deleted files. • Recover formated disks. • Repair detective disks." (Copied from the paste).
Acknowledgments. Preface. Introduction. Why this book is for you. Part one. Using PC backup. Part two. Using the data recovery utilities. Parte three. Using the speedup utilities. Part four. Using PC shell. Part five. Using the desktop manager. Index.
Keywords: MICROCOMPUTERS SOFTWARE; PC TOOLS DELUXE; UTILITAIRES -- LOGICIELS; UTILITIES -- COMPUTER PROGRAMS; PC TOOLS DELUXE -- COMPUTER PROGRAM